FAKTOR YANG BERHUBUNGAN DENGAN KECELAKAAN KERJA PADA PEMANEN KELAPA SAWIT DI DESA TERJUN GAJAH KECAMATAN BETARA KABUPATEN TANJUNG JABUNG BARAT - Mei Dani Al Dian; T Samsul Hilal (Sekolah Tinggi Pariwisata Mataram, 2023)
Work accidents can occur in various types of work, one of which occurs in the oil palm harvesting process. Workers who harvest oil palm are very likely to experience work accidents, including: falls, injuries caused by harvesting equipment, pricked by thorns, crushed by midribs, and crushed fresh fruit bunches, which can cause disability and even death. The purpose of this study was to determine the factors associated with the incidence of work accidents in oil palm harvesters in the village of Gajah Gajah. This research is a quantitative research with a cross sectional approach. This research was conducted in the Village of Gajah Subdistrict, Betara District, Tanjung Jabung Barat Regency in January 2022. The sample of the study was oil palm harvester workers in the Waterfall Village of Gajah. The number of samples in this study were 67 people. The instrument of this research is a questionnaire. The data collected were analyzed univariately and bivariately by using the chi square statistical test. Univariate results showed that 61.2% of respondents had experienced work accidents, 88.1% of respondents had long working periods, 44.8% of respondents were not good at using personal protective equipment and 53.7% of respondents had poor knowledge. The results of the bivariate analysis showed that there was a relationship between the use of personal protective equipment (p=0.000) and knowledge (p=0.000) with work accidents in oil palm workers. there is no relationship between years of service (p=0.711) and work accidents for oil palm workers.